Security of the Java Execution environment in e-business applications for SMEs - BM Tonis, Rocsana; Bucea-Manea-Tonis, Radu (Annals of Spiru Haret University. Economic Series, 2010)
Web space is currently inherent in any business activity, from SMEs to international holdings. In this context security of e-business applications becomes an issue intensively studied by the scientific literature. Currently the Java programming language is the most popular among software developers. The paper studies new elements of security, mainly for the Java environment. Other topics studied in this article refer to attack targets, fundamental threats against computer systems, means of facilitating security attacks and Java execution security environment. The case study demonstrates the impossibility of using a Java apllet over web to access files and folders structure on the host systems. Using Java Web environment is the security strength of e-business applications.